Atividade antimicrobiana in vitro e potencial probiótico de Bifidobacterium e Lactobacillus contra espécies de Clostridium - MONTEIRO, Cinara Regina Aragão Vieira (2018)
Clostridium species, mainly C. butyricum, C. difficile, and C. perfringens, are agents of infectious disease resulting from intestinal dysbiosis. In many cases, recurrence can occur after antibiotics, indicating the need for novel therapeutic options that act on the pathogens and also restore the microbiota. Herein, the in vitro antimicrobial activity and probiotic potential of clinical and reference strains of Bifidobacterium and Lactobacillus were investigated against pathogenic species of Clostridium. The antimicrobial activity was evaluated by the agar spot test and inhibition of gas production. Then, the probiotic potential of selected strains was assessed by analyzing their coaggregation ability, adhesive properties to host cells and mucin, tolerance to acidic pH and bile salts, and antimicrobial susceptibility profiles. Lactobacillus plantarum ATCC 8014 was the most promising strain based on its inhibitory activity against Clostridium spp. In addition, this strain met criteria to be considered a probiotic based on its coaggregation ability, adhesive properties, and tolerance to harsh conditions of pH and bile acid salts. Overall, the results indicate that among the studied strains, L. plantarum ATCC 8014 presents probiotic potential for controlling infections by the Clostridium species studied and should be further evaluated in in vivo animal studies.